PELAKSANAAN PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH ( STUDI DI KOTA PEMATANGSIANTAR) - HENRY SINAGA (PREMISE LAW JURNAL, 2013)
The implementation of collecting BPHTB (Tax on Land and Building Rights Acquisition) after the imposition of Law No. 28/2009 on Regional Tax and Regional Retribution, had caused a problem at Pematangsiantar. The problem arouse because Pematangsiantar Regional Administration collected BPHTB without following the regional regulation as it is stipulated in Law No. 28/2009 on Regional Taxes and Retribution. The central government states that the act of collecting taxes is contrary to the prevailing rules. In consequence, due to the public objection, the tax return was paid back to taxpayers. It is recommended that the central government shoud make transitional provisions in enacting legal provisions, Pematangsiantar Regional Administration should be careful in collecting taxes from people, and taxpayers should always control any kinds of tax collection by the government. Kata kunci : Implementation of Tax Collection, BPHTB, at Pematangsiantar